2005
DOI: 10.1121/1.1828551
|View full text |Cite
|
Sign up to set email alerts
|

Controlled ultrasound tissue erosion: The role of dynamic interaction between insonation and microbubble activity

Abstract: Previous studies showed that ultrasound can mechanically remove tissue in a localized, controlled manner. Moreover, enhanced acoustic backscatter is highly correlated with the erosion process. "Initiation" and "extinction" of this highly backscattering environment were studied in this paper. The relationship between initiation and erosion, variability of initiation and extinction, and effects of pulse intensity and gas saturation on time to initiation (initiation delay time) were investigated. A 788-kHz single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
159
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 178 publications
(162 citation statements)
references
References 32 publications
2
159
1
Order By: Relevance
“…In FUS-induced BBB opening, 20,[32][33][34][35][36][37] sonothrombolysis, [38][39][40][41][42] and histotripsy 43,44 studies, correlations between the cavitation activity measured using a single-element passive cavitation detector (PCD) and treatment outcome have been reported. Moreover, microbubble emissions have been used to select treatment pressures 36 and modulate them in real-time between subsequent therapy pulses 35 during FUS-induced BBB opening.…”
Section: Introductionmentioning
confidence: 99%
“…In FUS-induced BBB opening, 20,[32][33][34][35][36][37] sonothrombolysis, [38][39][40][41][42] and histotripsy 43,44 studies, correlations between the cavitation activity measured using a single-element passive cavitation detector (PCD) and treatment outcome have been reported. Moreover, microbubble emissions have been used to select treatment pressures 36 and modulate them in real-time between subsequent therapy pulses 35 during FUS-induced BBB opening.…”
Section: Introductionmentioning
confidence: 99%
“…11 The cavitation associated with histotripsy effects is described as a "bubble cloud," which has only been observed at pressure excursions much greater than inertial cavitation thresholds determined for similar frequency and pulse lengths in water. 12,13 A bubble cloud may be initiated during any pulse in a sequence of thousands of pulses, 12 although all incident pulses are essentially identical. This observation is evidence that bubble cloud initiation is a probabilistic phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Within solid organs (ie, prostate parenchyma, renal cortex), this process mechanically disrupts tissue structures such that the cumulative effect of multiple histotripsy bursts is conversion of the targeted tissue into a liquefied homogenate of subcellular debris. 2,3 Interestingly, some structures, such as the collecting system of the kidney, appear to be resistant to cavitational damage, while others, such as the renal medulla, necessitate greater numbers of histotripsy pulses to induce histologic injury, suggesting a varying threshold of cavitational effect based on tissue characteristics. 4 Previously, we have demonstrated that histotripsy is an effective noninvasive technology for prostate tissue ablation and debulking in the canine model.…”
mentioning
confidence: 99%